Adhesion and protective properties of electrospun PVA/ES composites obtained by using spiral disk spinnerets. Issue 14 (September 2017) - Zhao, Chuchu; Lu, Yao; Pan, Zhijuan
The parameters of electrospinning polyvinylalcohol (PVA) of different molecular weights using spiral disk spinnerets were explored. Ethylene-propylene side-by-side (ES) nonwoven was used as the substrate. Electrospun PVA/ES composite membranes were fabricated by laminating a nanofiber web onto the nonwoven substrate via the hot-press method. The adhesion properties between the PVA nanofiber mat and the ES nonwoven were studied. The results showed that the adhesion properties were significantly affected by temperature, pressure, and processing time. The resultant composite membranes, when treated at 145℃ with a pressure of 100 Pa for 10 minutes, exhibited a preferable adhesion energy of 7.95 J/m 2 and a maximum peeling strength of 20.17 cN, as well as a maximum air permeability of 73.92 dm 3 /(m 2 s). Simultaneously, the effect of electrospinning time on the characteristics of PVA/ES composites was also explored. The filtration efficiency increased with the prolongation of the electrospinning time, whereas the air permeability decreased. All of the samples were grade A in terms of the electrostatic half-life period (which was less than two seconds), and the softness slowly declined with the addition of nanofibrous layers. The breaking stress, the initial modulus, and the elongation were enhanced with the prolongation of electrospinning time.